Cost management as an efficiency tool within the scope of the Public Ministry of the State of Rio Grande do Norte (Research, Society and Development, 2020)
The current research has the purpose of studying the costs with the electric energy service within the scope of the Public Ministry of the State of Rio Grande do Norte (MPRN), from January to August 2018, in order to obtain a managerial diagnosis, that makes it possible to propose actions to reduce the costs of this service. The research approach is characterized as quali-quantitative; in relation to the objectives, it is classified as descriptive and explanatory, and, as for the procedures, as documentary research and case study. The study presents a diagnosis of the expense with the electric energy service and pointed out management measures to reduce it, considering the current institutional budget restrictions. The main results point to aggregations of 3 (three) counties, reduction of the demand contracted with Cosern of the headquarters building of the Natal Prosecutor's Offices and implementation of suggestions of good practices, of low cost, to reduce energy consumption in the institutional scope of the MPRN.